Program Sakera Jempol (Sadari Kekerasan Perempuan dan Anak dengan Jemput Bola) Kabupaten Pasuruan Perspektif Yuridis - Na'mah, Hadaita (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2018)
This article examines the implementation of the Sakera Jempol program (Realizing the Violence of Women and Children with Ball Pick) in Pasuruan Regency and the Effectiveness of Law No. 23 of 2004 concerning the Elimination of Domestic Violence Against the Government’s Pasuruan Regency program. The data of this study are collected from observation, interviews, and documentation. Data are then analyzed using descriptive methods with inductive mindset, which describe the results of the research systematically and then seen using a juridical perspective. Based on data in the field, the Sakera Jempol Program is a program for handling victims of domestic violence, such as health services, counseling, rehabilitation, and legal assistance. The effectiveness of this program in reducing the number of violence, seen from the graph of the distribution of the number of cases of violence against women and children in the 2015-2018 period, succeeded in reducing cases from 68 cases to 21 cases of Domestic Violence (KDRT). The speed of handling victims of domestic violence is seen from the graph of the speed of handling cases of violence against women and children in the 2015-2018 period, from 5 days to 1 day. This program, if viewed from the reporting and protection stages, the handling phase, and the rehabilitation phase, is in accordance with Law No. 23 of 2004 concerning the Elimination of Domestic Violence. [Artikel ini mengkaji pelaksanaan program Sakera Jempol (Sadari Kekerasan Perempuan dan Anak dengan Jemput Bola) Kabupaten Pasuruan dan Efektivitas Undang-Undang No 23 Tahun 2004 Tentang Penghapusan Kekerasan dalam Rumah tangga Terhadap program pemerintah Kabupaten Pasuruan tersebut. Data penelitian ini dihimpun dari observasi, wawancara, dan dokumentasi. Data kemudian dianalisis menggunakan metode deskriptif dengan pola pikir induktif, yakni menggambarkan hasil penelitian secara sistematis kemudian dilihat menggunakan perspektif yuridis. Berdasarkan data di lapangan, Program Sakera Jempol adalah program penanganan korban Kekerasan dalam Rumah Tangga, seperti pelayanan kesehatan, konseling, rehabilitasi, dan pendampingan hukum. Efektivitas program ini dalam menurunkan angka kekerasan, dilihat dari grafik distribusi jumlah kasus kekerasan perempuan dan anak periode 2015-2018, berhasil menurunkan kasus dari 68 kasus menjadi 21 kasus Kekerasan Dalam Rumah Tangga (KDRT). Kecepatan waktu penanganan korban KDRT, dilihat dari grafik kecepatan penanganan kasus kekerasan perempuan dan anak pada periode 2015-2018, dari 5 hari menjadi 1 hari saja. Program ini, jika dilihat dari tahap pelaporan dan perlindungan, tahap penanganan, dan Tahap rehabilitasi, telah sesuai dengan Undang-Undang No 23 Tahun 2004 Tentang Penghapusan Kekerasan Dalam Rumah Tangga. ]